Thermodynamic and kinetic verification of tetra-n-butyl ammonium nitrate (TBANO(3)) as a promoter for the clathrate process applicable to precombustion carbon dioxide capture - Babu, Ponnivalavan; Yao, Minghuang; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Environmental Science & Technology, 2014)
In this study, tetra-n-butyl ammonium nitrate (TBANO(3)) is evaluated as a promoter for precombustion capture of CO2 via hydrate formation. New hydrate phase equilibrium data for fuel gas (CO2/H-2) mixture in presence of TBANO(3) of various concentrations of 0.5, 1.0, 2.0, 3.0, and 3.7 mol % was determined and presented. Heat of hydrate dissociation was calculated using Clausius-Clapeyron equation and as the concentration of TBANO(3) increases, the heat of hydrate dissociation also increases. Kinetic performance of TBANO(3) as a promoter at different concentrations was evaluated at 6.0 MPa and 274.2 K. Based on induction time, gas uptake, separation factor, hydrate phase CO2 composition, and rate of hydrate growth, 1.0 mol % TBANO(3) solution was found to be the optimum concentration at the experimental conditions of 6.0 MPa and 274.2 K for gas hydrate formation. A 93.0 mol % CO2 rich stream can be produced with a gas uptake of 0.0132 mol of gas/mol of water after one stage of hydrate formation in the presence of 1.0 mol % TBANO(3) solution. Solubility measurements and microscopic images of kinetic measurements provide further insights to understand the reason for 1.0 mol % TBANO(3) to be the optimum concentration.